Design and Implementation of Automated irrigation system using ZIGBEE and GSM (International Journal of Scientific Research and Management (IJSRM), 2015)
The objective of this paper is to represent the Automated irrigation system using ZIGBEE and GSM for agricultural crop. In these system use the Wireless Technology. The system has represented the wireless sensor network of soil-moisture, temperature and humidity sensor and water level sensor placed into root zone of the plant. In traditional approach to measure these factors in an agricultural environment meant individuals manually taking measurements and checking them at various times. This paper includes the monitoring of the system using zigbee and gsm.